2019
DOI: 10.1029/2018gl080940
|View full text |Cite
|
Sign up to set email alerts
|

Global Meridional Overturning Circulation Inferred From a Data‐Constrained Ocean & Sea‐Ice Model

Abstract: Our current understanding of the global meridional overturning circulation (GMOC) is revisited using a surface‐forced ocean model simulation constrained by global hydrographic data. The derived GMOC is qualitatively consistent with previous observation‐based studies and further provides enhanced spatial details in the sources, transformations, and transports of major global water masses including in poorly observed regions. Several important but relatively underexplored aspects of the GMOC are highlighted, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…The drivers of this circulation still remain under discussion, with debate centering around the proportion of water mass transformation between light and dense waters occurring in the high-latitude North Atlantic and the Southern Ocean and through diapycnal upwelling at lower latitudes (Cessi, 2019;Ferrari & Wunsch, 2009;Ferrari et al, 2017;Gnanadesikan, 1999;Talley, 2013;Lee et al, 2018;Marshall & Speer, 2012;Thompson et al, 2016;Toggweiler et al, 2019;Newsom & Thompson, 2018). The drivers of this circulation still remain under discussion, with debate centering around the proportion of water mass transformation between light and dense waters occurring in the high-latitude North Atlantic and the Southern Ocean and through diapycnal upwelling at lower latitudes (Cessi, 2019;Ferrari & Wunsch, 2009;Ferrari et al, 2017;Gnanadesikan, 1999;Talley, 2013;Lee et al, 2018;Marshall & Speer, 2012;Thompson et al, 2016;Toggweiler et al, 2019;Newsom & Thompson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The drivers of this circulation still remain under discussion, with debate centering around the proportion of water mass transformation between light and dense waters occurring in the high-latitude North Atlantic and the Southern Ocean and through diapycnal upwelling at lower latitudes (Cessi, 2019;Ferrari & Wunsch, 2009;Ferrari et al, 2017;Gnanadesikan, 1999;Talley, 2013;Lee et al, 2018;Marshall & Speer, 2012;Thompson et al, 2016;Toggweiler et al, 2019;Newsom & Thompson, 2018). The drivers of this circulation still remain under discussion, with debate centering around the proportion of water mass transformation between light and dense waters occurring in the high-latitude North Atlantic and the Southern Ocean and through diapycnal upwelling at lower latitudes (Cessi, 2019;Ferrari & Wunsch, 2009;Ferrari et al, 2017;Gnanadesikan, 1999;Talley, 2013;Lee et al, 2018;Marshall & Speer, 2012;Thompson et al, 2016;Toggweiler et al, 2019;Newsom & Thompson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Both the warm water route (Donners & Drijfhout, ; Lee et al, ; Speich et al, ; Speich et al, ; Weijer et al, ) and the cold water route (Macdonald, ; Sloyan & Rintoul, ; You, ) have found heavy favor in past studies. Two recent studies, however, suggest a more comparable role for the pathways, while still attributing a larger contribution to the warm route (Rodrigues et al, ; Rühs et al, ) The divergent estimates of the cold and warm water route contributions can be partially explained by the use of different data sets and methods, as well as the use of coarse‐resolution models (Donners & Drijfhout, ; Rühs et al, )…”
Section: Introductionmentioning
confidence: 99%
“…Interest in these competing sources stems from an expectation that the prevalence of one over the other affects the variability and stability of the AMOC because of their influence on deep water formation in the Both the warm water route (Donners & Drijfhout, 2004;Lee et al, 2019;Speich et al, 2001;Speich et al, 2007;Weijer et al, 2002) and the cold water route (Macdonald, 1998;Sloyan & Rintoul, 2001;You, 2002) have found heavy favor in past studies. Two recent studies, however, suggest a more comparable role for the pathways, while still attributing a larger contribution to the warm route (Rodrigues et al, 2010;Rühs et al, 2019) The divergent estimates of the cold and warm water route contributions can be partially explained by the use of different data sets and methods, as well as the use of coarse-resolution models (Donners & Drijfhout, 2004;Rühs et al, 2019) The majority of these past studies have addressed the contributions of the cold and warm water routes from a modeling perspective, either in the Eulerian or Lagrangian framework.…”
Section: Introductionmentioning
confidence: 99%
“…Although meso‐scale direction and velocity of currents at lower bathyal and abyssal depths are less well known, they form part of the thermohaline global meridional overturning circulation. Cold (~1°C) and oxygen‐rich Antarctic Bottom Water flows northwards across southern seafloors where it eventually diffuses into shallower waters to form deoxygenated but more saline Indian and Pacific Deep Waters which return southwards (~2,000 m at 40°S) to upwell in the Southern Ocean (Lee et al, ; Talley, ). Water masses in the North Atlantic have been shown to be spatially dynamic at decadal (Yasuhara et al, ) to millennial temporal scales (Yasuhara, Hunt, Cronin, & Okahashi, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the Tasman Sea, the same water mass enters via two routes, from the SE as eddies and from the north as a current, where AAIW in the SW Pacific has become entrained by the East Australian Current (Davis, 2005;Ollitrault & de Verdiére, 2013). Although Deep Waters which return southwards (~2,000 m at 40°S) to upwell in the Southern Ocean (Lee et al, 2019;Talley, 2013). Water masses in the North Atlantic have been shown to be spatially dynamic at decadal (Yasuhara et al, 2019) to millennial temporal scales (Yasuhara, Hunt, Cronin, & Okahashi, 2009).…”
Section: F I G U R E 3 Key Variable Responses Using Final Rad Modelsmentioning
confidence: 99%